ASSESSMENT OF SECONDARY DENTINOGENESIS ON PERMANENT MOLARS – A MICRO-CT STUDY - Ralitsa Bogovska-Gigova (Journal of IMAB)
Purpose: This study quantitatively evaluates secondary dentinogenesis in permanent molars by comparing the volume and thickness of enamel, coronal dentin, and pulp chamber in immature and mature teeth. Material and methods: Forty-eight extracted third molars were analyzed using micro-computed tomography (micro-CT). The sample included 24 mature (from patients aged 25-30) and 24 immature teeth (from patients aged 15-18), all without caries lesions or other defects. Morphometric measurements assessed the volumes of enamel, dentin, and the pulp chamber, as well as the thickness of enamel and dentin in the area of the mesiobuccal (MB) cusp and central pit. Results: The results revealed no significant difference in enamel volume or thickness between the two groups. However, mature teeth exhibited a significantly greater coronal dentin volume (309.884 ± 42.982 mm³ vs. 250.560 ± 47.025 mm³, p = 0.001) as well as increased thickness of the dentin at the MB cusp (p = 0.003) and central pit (p = 0.001). Additionally, the pulp chamber volume was significantly reduced in mature teeth (13.712 ± 3.443 mm³ vs. 19.759 ± 4.883 mm³, p<0.001). Conclusion: These findings highlight the progressive deposition of secondary dentin with age, which reduces the size of the pulp chamber and increases dentin thickness, particularly in high-risk areas like the MB cusp. This study underscores the importance of understanding structural differences between immature and mature molars for informed clinical decision-making in caries management and minimally invasive dentistry.